Imunoexpressão de Efrina-A1, Efrina-2 e EphA1 em queilites actínicas e carcinomas de células escamosas de lábio inferior - Lopes, Natália Vitória de Araújo (2025)
Actinic cheilitis (AC) is a potentially malignant disorder lesion that affects the lips, resulting from chronic and prolonged exposure to ultraviolet radiation. This persistent exposure may contribute to genetic damages accumulation that promotes malignant transformation into squamous cell carcinoma (SCC). The cellular and molecular mechanisms involved in this process, although intensely investigated, are still poorly understood. A series of studies have highlighted ephrins and their receptors (Ephs) as important proteins involved in the development and progression of several cancers, but their possible participation in lip carcinogenesis is not well established. Therefore, this study analyzed the immunoexpression of Ephrin-A1, Ephrin-B2 and EphA1 in ACs and SCCs of the lower lip. Thirty cases of AC and thirty cases of lip SCC were selected for clinical, morphological and immunohistochemical investigation. Clinical data (sex and age, tumor size/extension, regional lymph node metastasis and clinical stage) were collected in biopsy request forms and medical records. For the morphological analysis, the degree of epithelial dysplasia in ACs cases and the histopathological degree of malignancy at the invasive front of SCC were evaluated. In the immunohistochemical study, the percentages of positive epithelial cells (nucleus and cytoplasm) for Ephrin-A1, Ephrin-B2 and EphA1 were established in 5 microscopic fields of the epithelial lining of ACs and in 10 fields of the SCC invasion front. Results were submitted to non-parametric Mann-Whitney test and Spearman correlation test (p < 0.05). Cytoplasmic immunoexpression of Ephrin-A1, Ephrin-B2 and EphA1 were observed in all cases of AC and SCC analyzed. Compared to ACs, SCCs showed lower median percentages of cytoplasmic positivity for Eprhin-A1 (p = 0.005) and Ephrin-B2 (p < 0.001). Nuclear expressions of Ephrin-A1 and Ephrin-B2 were more frequently observed in ACs, with lower median percentages of positivity in both groups studied. With respect to EphA1, nuclear immunoreactivity was identified in all ACs cases and in most SCCs (n = 27; 90.0%), with significantly lower positivity percentages in the latter (p = 0.002). Considering the clinicopathological parameters of the lesions, lower cytoplasmatic expression of Ephrin-B2 was observed in ACs with high degree of epithelial dysplasia (p = 0.029), as well as lower nuclear expression of EphA1 in SCCs classified as T2–T4 (p = 0.010) and with high histological degree (p = 0.004). In SCCs, cytoplasmic expressions of EphA1 and Ephrin-B2 showed a statistically significant moderate positive correlation (r = 0.378; p = 0.039). In conclusion, the results of this study suggest the involvement of Ephrin-A1, Ephrin-B2 and EphA1 in the pathogenesis of lower lip ACs and SCCs. In particular, reductions in the nuclear translocation of EphA1 and in the cytoplasmatic expression of Ephrin-A1 and -B2 could contribute to malignant transformation of ACs and, eventually, promote the progression of lower lip CCEs. In this process, EphA1 may function as a tumor suppressive role within the nucleus of epithelial cells